Processed Meat Production in 3 Dimensional (3D) Printing Technology - Celalettin Değerli (Turkish Journal of Agriculture: Food Science and Technology, 2020)
Both industrial and academic fields, 3-dimensional (3D) printing of food materials is one of the most interesting subjects. Taking attention with its errorless product handling, easy adaptation for personalized nutrition and sustainable properties, 3D printing of foods is also having a potential in the field of health and nutritious products. In this review, potential connection between meat products, personalized nutrition and 3D printing were mentioned briefly. After that, basic working principles of 3D printers and applicability for meat products were explained. Assessment of meat process waste, advantages and limitations, concept of printability and studies in this field were explained and discussed in details.